THE INFLUENCE OF IMPLEMENTING MODULAR CONSTRUCTION METHODS ON TIME AND COST EFFICIENCY IN BUILDING CONSTRUCTION PROJECTS - Fahlevi, Riza; Manurung, Edison Hatoguan; Purba, Agus (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to analyze the effect of implementing the modular construction method on time and cost efficiency in building construction projects. The technique used in this study is a quantitative approach with data collection through documentation research and interviews with project managers, contractors, and technical teams. The study's results indicate that implementing the modular construction method can save project time by around 20% to 28% and costs by 20% to 24%. These savings are obtained by reducing work time on-site and carrying out several jobs off-site parallel. However, the main challenges are higher initial costs and difficulties adapting modular designs to local conditions. Limited knowledge of this method among contractors is also an obstacle to its implementation. In conclusion, the modular construction method can increase time and cost efficiency in construction projects, but training and increased knowledge are needed for its implementation to be more optimal